2023
DOI: 10.1002/adma.202208960
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Applications in Electronic Devices of Lattice‐Aligned Gallium Oxynitride Nanolayer on Gallium Nitride

Abstract: Gallium nitride (GaN), a promising alternative semiconductor to Si, is widely used in photoelectronic and electronic technologies. However, the vulnerability of the GaN surface is a critical restriction that hinders the development of GaN‐based devices, especially in terms of device stability and reliability. In this study, this challenge is overcome by converting the GaN surface into a gallium oxynitride (GaON) epitaxial nanolayer through an in situ two‐step “oxidation–reconfiguration” process. The O plasma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…28 The high-energy oxygen atom bonds with the Ga atom, forming Ga−O bonds and resulting in the formation of GaON with a larger band gap (E g ) than that of GaN, as illustrated in Figure 5b. The energetically favorable and thermodynamic stable bond formation of Ga−O compared to that of Ga−N can be attributed to the lower electron affinity of O than N. 28 Consequently, several O atoms can replace the position of N atoms, while others become interstitial atoms. Analysis of Ga 3d and O 1s core levels in the X-ray photoelectron spectra (XPS) of the GaN sample with OPT is shown in Figure S3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The high-energy oxygen atom bonds with the Ga atom, forming Ga−O bonds and resulting in the formation of GaON with a larger band gap (E g ) than that of GaN, as illustrated in Figure 5b. The energetically favorable and thermodynamic stable bond formation of Ga−O compared to that of Ga−N can be attributed to the lower electron affinity of O than N. 28 Consequently, several O atoms can replace the position of N atoms, while others become interstitial atoms. Analysis of Ga 3d and O 1s core levels in the X-ray photoelectron spectra (XPS) of the GaN sample with OPT is shown in Figure S3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The root-mean-square (RMS) values of the AFM images revealed that the ICP etching resulted in a rather rough etching interface, while the OPT improved the surface roughness to a certain extent. The schematic diagram of the formation of the GaON nanolayer by OPT is presented in Figure a . The high-energy oxygen atom bonds with the Ga atom, forming Ga–O bonds and resulting in the formation of GaON with a larger band gap ( E g ) than that of GaN, as illustrated in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…[26] For the oxidation of GaN thin films, Yamada and Chen et al have been demonstrated that the translation from hexagonal GaN to monoclinic 𝛽Ga 2 O 3 in hightemperature oxidation processes with oxygen substituting for nitrogen usually occurred at the penetration dislocation inside GaN films and proposed an oxidation mechanism near the penetration dislocation. [27,28] That is, GaO x generated by high-temperature oxidation migrates through the surface, deposits near the penetration dislocation, and eventually forms massive grains. Since the penetration dislocation density of GaN films is usually about 10 8 cm −2 , the surface roughness of GaO x films formed by hightemperature oxidation is relatively high.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Previous works reveal that the pristine p-GaN/electrolyte interface may suffer large charge-transfer impedance raised by charge trapping from surface states, [20] leading to poor efficiency of the reduction reaction. With the help from co-catalyst loading on surface, the decorated adlayer may act as passivation layer to eliminate the charge-trapping effect, [20][21][22] enabling fast charge transfer from GaN to the adlayer. In addition, such adlayer may also significantly change the reaction activity at nanowire surface by offering plenty of active sites.…”
Section: Working Principles Of the Bipolar-junction Photoelectrodementioning
confidence: 99%